Of sadhus and spinners : Australian encounters with India - Bennett, Bruce (New Delhi : HarperCollins Publishers India, a joint venture with The India Today Group, 2009)
Stories based on the problems faced by Australians in India and East Indians in Australia.
The Mohammedan mother / John Lang -- Our nearest great country / Alfred Deakin -- The soul of the melon man / Mary C. Elkington -- My friend, the maharajah / Louis Esson -- Black and white / R. Francis Strangman -- The Khyber pass and a kidnapping / Mollie Skinner -- A democrat on the Ganges / Manning Clark -- Mrs. James Greene / Ethel Anderson -- Kumari / Mena Abdullah and Ray Mathew -- Sadhus and sahibs / Christopher Koch -- The clothesline in the Himalayas / Vicki Viidikas -- Meeting Mister Ghosh / Haydn M. Williams -- The elephant stop / G.S. Sharat Chandra -- The strange business at Bombay and Madras / Dal Stivens -- Passage from India / Geoffrey Bewley -- A foot in the stream / David Malouf -- The guru / Satendra Nandan -- Monsoon / Inez Baranay -- Maisie goes to India / Joan London -- My sister's mother / Manik Datar -- A pocket full of stories / Sujatha Fernandes -- Masterpiece / Yasmine Gooneratne.
Short stories.
Keywords: Australians -- India -- Fiction; East Indians -- Australia -- Fiction; Short stories, Australian